Who Knows Who Knows What in the Group? The Effects of Communication Network Centralities, Use of Digital Knowledge Repositories, and Work Remoteness on Organizational Members’ Accuracy in Expertise Recognition - Su, Chunke (Communication Research, 2012)
Organizational members vary in their ability to accurately recognize each other’s expertise. The goal of this study is to extend transactive memory theory to understand how organizational group members develop accurate perceptions of others’ knowledge through a multidimensional access to expertise cues. Specifically, this study examines how a group member’s accuracy in expertise recognition is influenced by one’s centralities in the communication network, use of digital knowledge repositories, and work remoteness. By analyzing data collected from 208 individuals from 17 organizational groups, this study found that a member’s accuracy in expertise recognition was positively influenced by one’s degree centrality in the communication network and negatively influenced by the extent to which one’s work was done remotely. Furthermore, there was an interaction effect between work remoteness and use of digital knowledge repositories such that the negative influence of work remoteness on expertise recognition was weaker when members used digital knowledge repositories.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjExNDMzODI1